The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcvm.2022.858994
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Adult Triceps Skinfold Thickness and All-Cause, Cardiovascular and Cerebrovascular Mortality in NHANES 1999–2010: A Retrospective National Study

Abstract: Background:The association between triceps skinfold (TSF) thickness and mortality in previous studies was controversial. This study aimed to explore how TSF thickness affects all-cause, cardiovascular, and cerebrovascular mortality among the United States (U.S.) general population.MethodsOur research included 25,954 adults in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2010. Participants were categorized by the baseline TSF quartiles [quartile 1 (Q1): < 11.8, (Q2): 11.8–17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
(49 reference statements)
0
9
1
Order By: Relevance
“…At that time, small doses of nontobacco, reliable and safe nicotine preparations can be given to implement nicotine replacement therapy to gradually reduce withdrawal symptoms, so as to overcome the smoking habit [27,28] . In addition, other reports indicate that smoking has no significant correlation with recurrence of stroke [29] . However, many of the damages caused by smoking can be avoided or reduced by quitting smoking [30,31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, small doses of nontobacco, reliable and safe nicotine preparations can be given to implement nicotine replacement therapy to gradually reduce withdrawal symptoms, so as to overcome the smoking habit [27,28] . In addition, other reports indicate that smoking has no significant correlation with recurrence of stroke [29] . However, many of the damages caused by smoking can be avoided or reduced by quitting smoking [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…[27,28] In addition, other reports indicate that smoking has no significant correlation with recurrence of stroke. [29] However, many of the damages caused by smoking can be avoided or reduced by quitting smoking. [30,31] Therefore, smoking cessation intervention is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a predictive effect of lower triceps skinfold thickness on poor prognosis 24 . A previous study including 25,954 adults from the National Health and Nutrition Examination Survey showed that higher triceps skinfold thickness was associated with lower all‐cause and cardiovascular mortality independent of BMI and mid‐arm muscle circumference 25 . Triceps skinfold thickness, as an indicator of nutrition status, has been confirmed to identify the risk of malnutrition early and improve patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…24 A previous study including 25,954 adults from the National Health and Nutrition Examination Survey showed that higher triceps skinfold thickness was associated with lower all-cause and cardiovascular mortality independent of BMI and midarm muscle circumference. 25 Triceps skinfold thickness, as an indicator of nutrition status, has been confirmed to identify the risk of malnutrition early and improve patient prognosis. Therefore, triceps skinfold thickness is a reliable indicator of nutrition status in various disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 (Ref. [10][11][12][13][14][15][16][17][18][19][20]) summarizes the main results of the above studies.…”
Section: Subscapular and Triceps Skinfolds Thicknessmentioning
confidence: 99%